2014
DOI: 10.1111/cei.12270
|View full text |Cite
|
Sign up to set email alerts
|

Single cell-derived clones from human adipose stem cells present different immunomodulatory properties

Abstract: (7) CIBERobn (Fisiopatología de la Obesidad y la Nutrición CB12/03/30038) Instituto de Salud Carlos III, Spain. Corresponding author:Enrique Roche.Instituto de Bioingeniería, Universidad Miguel Hernández. Avda de la Universidad. 03202-Elche, SPAINThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Also, continuous culture in either FCS or hPL affected the distribution of ASCs within the subcategories of CD146 + and/or CD271 + cells. Whether and how this altered expression of the classic stem cell markers CD73 and CD105 reflects on the functionality of the ASCs is still uncertain, but CD73 has been suggested to be involved in differentiation [62] and regulation of the immune modulatory pathway together with CD105 [63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…Also, continuous culture in either FCS or hPL affected the distribution of ASCs within the subcategories of CD146 + and/or CD271 + cells. Whether and how this altered expression of the classic stem cell markers CD73 and CD105 reflects on the functionality of the ASCs is still uncertain, but CD73 has been suggested to be involved in differentiation [62] and regulation of the immune modulatory pathway together with CD105 [63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…Sempere et al examined human MSCs: the group showed results that provided mechanisms that may be involved with the in vivo MSC-mediated induction of tolerance, which to their point of view could be used therapeutically for reducing graft rejection [41]. Xie et al found that anti-inflammatory proteins, which are induced from xenografted hASCs, are capable of responding to host inflammatory signals [42].…”
Section: Immunogenicitymentioning
confidence: 99%
“…Recent advances in the ability to study single-cell transcriptomes can be leveraged to better understand the cellular composition of adipose tissue [11][12][13]. Single-cell transcriptomics of nonmature adipocytes in mouse fat has revealed specific populations of adipocyte stem cells primed to expand in response to adrenergic stimulation [13], stromal cells capable of inhibiting adipogenesis [11], and cells with enhanced adipogenic or fibro-inflammatory properties [14]. The use of single-cell transcriptomics to define mature adipocyte subtypes is complicated by the large size and high buoyancy of these cells, and the fact that the extensive proteolytic digestion required to isolate them from the adipose tissue compromises their viability and alters their phenotype [15].…”
Section: Introductionmentioning
confidence: 99%